DISPATCHING INDONESIAN WORKERS TO MALAYSIA: A STRATEGY TO OVERCOME THE POVERTY AND EDUCATION COST (Case Study of Indonesian Workers of Central Java with Phenomenology Approach) - Tjipto Subadi; - Samino (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2015)
The objectives of the research are describing 1) a dispatching model of Indonesian workers to Malaysia and 2) the core problems of Indonesian workers in Malaysia.  The research applied a phenomenology qualitative approach with focusing on micro social mobility. The subjects of theresearch were Indonesian workers and their family, government, head of neighborhood members, and the House of Representatives. It was located in Central Java. The techniques of the data collecting included observation, interviewing, and documentation. The data validation employed the first order understanding and second order understanding. The data were analyzed with aninteractive model: data reduction, data display, and conclusion. It could be concluded that 1) thedispatching model was using an exposure approach and bottom-up approach. An employment process of the Indonesian workers was in three stages: pre-, core-, and post-provisions of work. A strategy of overcoming the poverty and education cost used a religious approach and efficient financial management. 2) The problems of the workers covered that a) the employers treated mostof them violently; b) most of the workers’ contracts expired; and c) most of them used illegal passports (visiting passports) or documents so that they did got any protectionKeywords: Indonesian workers, overcoming, poverty, cost, education